Stabilitas Hasil Galur Baru Padi Sawah Preferensi Konsumen Sumatera Barat - ZEN, SYAHRUL (AGRITROP, 2007)
Total rice field area in West Sumatera is 221.165 ha. The largest portion of irrigated rice is on 0 – 1200 m asl.The major preference of Indonesia rice consumers, the West Sumatera consumers prefer high amylose content rice.The availability of rice variety with high amylose is very limited; consequently, the dominant varieties planted bythe farmers were Cisokan and IR 42 that has been cultivated for more than 1 0 years. By single variant analyze forgenotype yield data were absolutely different. According to average yield of 21 grows environment, SPR85163-5-1-2-4 line and S4362f-Kn-2-1-2 showed the sheet for each line 10 and 18% higher than Cisokan. The yield of bothvariants were 4.68 – 7.62 t/ha and 3.24 – 7.83 t/ha, with average of yield was 6.06 and 6.48 t/ha, whereas Cisokanyield was 3.32 – 7.89 t/ha with average of yield was 5.49 t/ha. According to data of turn yield and cross average ofenvironment grow SPR85163-5-1-2-4 line was superior in yield capacity and adaptation then Cisokan. In certainenvironment grow; line S4362f-Kn-2-1-2 had the lower sheet yield than Cisokan and SPR85163-5-1-2-4. Stabilityparameter analyze indicate that all genotype that were tested gave the stable respond to chance of condition in21 environment grow, SPR85163-5-1-2-4 line was more stable than line S4362f-Kn-2-1-2, that was indicated bycontribution of each. Interaction of variant component Genotype x environment (interaction of G x L) for eachcomponent was 15 and 23 %. The line of SPR85163-5-1-2-4 was able to yield 20% higher than line S4362f-Kn-2-1-2 and 26% Cisokan variety at Guguk environment (850 a above se level), while SPR85163-5-1-2-4 line has thebest result until 700 m above sea level.